UNIT 21.27 Genome‐Scale Mapping of DNase I Hypersensitivity. Issue 1 (July 2013) - John, Sam; Sabo, Peter J.; Canfield, Theresa K.; Lee, Kristen; Vong, Shinny; Weaver, Molly; Wang, Hao; Vierstra, Jeff; Reynolds, Alex P.; Thurman, Robert E.; Stamatoyannopoulos, John A.
Abstract: DNase I‐seq is a global and high‐resolution method that uses the nonspecific endonuclease DNase I to map chromatin accessibility. These accessible regions, designated as DNase I hypersensitive sites (DHSs), define the regulatory features, (e.g., promoters, enhancers, insulators, and locus control regions) of complex genomes. In this unit, methods are described for nuclei isolation, digestion of nuclei with limiting concentrations of DNase I, and the biochemical fractionation of DNase I hypersensitive sites in preparation for high‐throughput sequencing. DNase I‐seq is an unbiased and robust method that is not predicated on an a priori understanding of regulatory patterns or chromatin features. Curr. Protoc. Mol. Biol. 103:21.27.1–21.27.20. © 2013 by John Wiley & Sons, Inc.